Key factors increasing the trust and intention to adopt standard cloud-based applications. (2016) - Chen, Charlie C.; Nakayama, Makoto
Cloud-based applications enable agile implementation to facilitate timely organisational change. A generic standard cloud-based application like Google Docs is among the first to be considered for adoption. Thus, it is worthy to examine what factors influence trust and the intention of continuing use for such a cloud-based application. Unlike traditional, on-premise applications, familiarity is not an issue for trusting generic, simple cloud-based applications. Moreover, perceived risk is low enough that it has negative, as opposed to the usual positive, impact on trust and the intention of continuing use. The results of this study also imply that the agile adoption of standard cloud-based applications needs to consider factors, including perceived privacy control, system quality, and user satisfaction because these factors can increase the trust of users. Theoretical and practical implications were drawn from the findings of this study.